P38 MAPK signaling in M1 macrophages results in selective elimination of M2 macrophages by MEK inhibition. Issue 7 (20th July 2021) - Baumann, Daniel; Drebant, Jennifer; Hägele, Tanja; Burger, Luisa; Serger, Clara; Lauenstein, Claudia; Dudys, Przemyslaw; Erdmann, Gerrit; Offringa, Rienk
Abstract : M2 macrophages promote tumor progression and therapy resistance, whereas proimmunogenic M1 macrophages can contribute to the efficacy of cytostatic and immunotherapeutic strategies. The abundance of M2 macrophages in the immune infiltrate of many cancer types has prompted the search for strategies to target and eliminate this subset. From our prior experiments in syngeneic mouse tumor models, we learned that pharmacological inhibition of mitogen-activated protein kinase kinase (MEK) did not merely result in tumor cell death, but also in the modulation of the tumor immune infiltrate. This included a prominent decrease in the numbers of macrophages as well as an increase in the M1/M2 macrophage ratio. Investigation of the mechanism underlying this finding in primary murine macrophage cultures revealed that M2 macrophages are significantly more sensitive to MEK inhibition-induced cell death than their M1 counterparts. Further analyses showed that the p38 MAPK pathway, which is activated in M1 macrophages only, renders these cells resistant to death by MEK inhibition. In conclusion, the dependency of M2 macrophages on the MEK/extracellular-signal regulated kinase (ERK) pathway empowers MEK inhibitors to selectively eliminate this subset from the tumor microenvironment.